DINAMIKA MAKNA CINTA DALAM LAGU POPULER INDONESIA TAHUN 2023–2024: KAJIAN SEMANTIK - Novita Fitri Astuti (Universitas Hamzanwadi, 2026)
This study aims to describe the denotative and connotative meanings in three popular Indonesian songs, namely